2015
DOI: 10.1523/jneurosci.1878-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Neural Mechanisms Underlying Contextual Dependency of Subjective Values: Converging Evidence from Monkeys and Humans

Abstract: A major challenge for decision theory is to account for the instability of expressed preferences across time and context. Such variability could arise from specific properties of the brain system used to assign subjective values. Growing evidence has identified the ventromedial prefrontal cortex (VMPFC) as a key node of the human brain valuation system. Here, we first replicate this observation with an fMRI study in humans showing that subjective values of painting pictures, as expressed in explicit pleasantne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
34
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 44 publications
(12 reference statements)
8
34
1
Order By: Relevance
“…A striking parallel was found at the neural level, with the prior preference being reflected in the baseline activity of valuation regions including the vmPFC, ventral striatum and posterior cingulate cortex. This is in line with a previous study showing that baseline vmPFC activity is sensitive to contextual factors, both in humans and monkeys, and provide a bias in subsequent valuation processes (Abitbol et al, 2015). Other contextual manipulations were found to modulate vmPFC activity and subsequent valuation, for instance mood induction has been shown to affect reward-related vmPFC activity (Young and Nusslock, 2016).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…A striking parallel was found at the neural level, with the prior preference being reflected in the baseline activity of valuation regions including the vmPFC, ventral striatum and posterior cingulate cortex. This is in line with a previous study showing that baseline vmPFC activity is sensitive to contextual factors, both in humans and monkeys, and provide a bias in subsequent valuation processes (Abitbol et al, 2015). Other contextual manipulations were found to modulate vmPFC activity and subsequent valuation, for instance mood induction has been shown to affect reward-related vmPFC activity (Young and Nusslock, 2016).…”
Section: Discussionsupporting
confidence: 93%
“…(Chib et al, 2009; Hare et al, 2010; Lebreton et al, 2009; Plassmann et al, 2007). Such value coding was observed not only during choice but also in the absence of choice, during passive viewing of items presented in the attentional focus or when performing a distractive task on these items (Lebreton et al, 2009; Levy et al, 2011; Abitbol et al, 2015). …”
Section: Introductionmentioning
confidence: 92%
“…Besides, HERs modulated value encoding in a multiplicative manner. Our results thus differ from a previously reported vmPFC baseline-shift additive effect in pleasantness ratings (Abitbol et al, 2015;Lopez-Persem et al, 2020). Altogether, our results indicate that part of the unspecified 'neural noise' driving fluctuations in choice consistency (Padoa-Schioppa, 2013;Kurtz-David et al, 2019;Webb et al, 2019) comes from the interaction between interoceptive self-related processes, indexed by neural monitoring of cardiac signals, and the neural encoding of subjective value.…”
Section: Discussioncontrasting
confidence: 99%
“…We tested this hypothesis in anatomical masks of the vmPFC and dlPFC based on the HarvardOxford Cortical Atlas (Desikan et al, 2006). The vmPFC mask comprised the bilateral vmPFC that is part of the brain's valuation system (Bartra et al, 2013;Clithero and Rangel, 2014;Abitbol et al, 2015;Pessiglione and Delgado, 2015) and has been shown to integrate taste and health values in the dietary selfcontrol paradigm (Hare et al, 2009(Hare et al, , 2011(Hare et al, , 2014Foerde et al, 2015;Maier et al, 2015) as well as the separate characteristics of multiattribute choices in other, nonfood domains (Kahnt et al, 2011;Rudorf and Hare, 2014). Our second anatomical mask included the region of the left dlPFC that has been presumed to modulate activity in the vmPFC during self-control choices (Hare et al, 2009(Hare et al, , 2011(Hare et al, , 2014.…”
Section: Hrv and Bold Activity During Self-controlmentioning
confidence: 99%